Optimal joint motion for complicated welding geometry by a redundant robotic system. Issue 5 (3rd May 2020) - Shahabi, M.; Ghariblu, H.
ABSTRACT: The main objective of this article is to develop a redundancy-resolution algorithm to optimize the joint motion of a redundant robotic welding system. First, the joint limit avoidance (JLA) and singularity avoidance (SGA) optimizations are employed. Owing to the complicated geometry of the welding path, despite using JLA and SGA optimizations, some constraints, such as joint angles, violate their allowable limits. Hence, functional redundancy (FNR) is employed as the best solution because it has no effect on the welding electrode direction. In this article, the FNR is used as an augmented task, which changes the desired path without affecting the electrode direction. To select the best FNR angle, two indices, i.e. the minimum joint angles movement and the singularity avoidance indices, are introduced. Simulation results show that the planned path using FNR not only satisfies all constraints, but also is smooth.